Simulation of the concomitant process of nucleation-growth-coarsening of Al2Cu particles in a 319 foundry aluminum alloy. (23rd April 2015) - Martinez, R; Larouche, D; Cailletaud, G; Guillot, I; Massinon, D
Abstract: The precipitation of Al2 Cu particles in a 319 T7 aluminum alloy has been modeled. A theoretical approach enables the concomitant computation of nucleation, growth and coarsening. The framework is based on an implicit scheme using the finite differences. The equation of continuity is discretized in time and space in order to obtain a matricial form. The inversion of a tridiagonal matrix gives way to determining the evolution of the size distribution of Al2 Cu particles at t +Δ t . The fluxes of in-between the boundaries are computed in order to respect the conservation of the mass of the system, as well as the fluxes at the boundaries. The essential results of the model are compared to TEM measurements. Simulations provide quantitative features on the impact of the cooling rate on the size distribution of particles. They also provide results in agreement with the TEM measurements. This kind of multiscale approach allows new perspectives to be examined in the process of designing highly loaded components such as cylinder heads. It enables a more precise prediction of the microstructure and its evolution as a function of continuous cooling rates.